Розвиток теоретичної електротехніки в Інституті електродинаміки НАН України (1991–2017 рр.) - Лавріненко, Ольга Валеріївна (Гілея, 2019)
Робота присвячена дослідженню розвитку важливої галузевої науки – теоретичної електротехніки в провідному науковому інституті НАН України Інституті електродинаміки у період з 1991 по 2017 рік. Автором проведено послідовний проблемно-хронологічний аналіз залучених архівних матеріалів та наукових джерел з метою історичної реконструкції розвитку теоретичної електротехніки в ІЕ НАН на етапах формування свого наукового шляху, пошуку нових ідей та їх практичної реалізації в сучасному історичному періоді розвитку академічної науки в Україні. Для порівняльного аналізу науково-дослідної тематики монографій та авторефератів дисертаційних робіт, захищених науковцями інституту, було використано статистичний метод дослідження.

The work is devoted to the study of the development of an important branch science - theoretical electrical engineering at the leading scientific institute of the National Academy of Sciences of Ukraine Institute of Electrodynamics in the period from 1991 to 2017. The author carried out a sequential problem-chronological analysis of the attracted archival materials and scientific sources for the purpose of historical reconstruction of theoretical electrical engineering development at the EI NAS at the stages of formation of its scientific path, the search for new ideas and their practical implementation in the modern historical period of the development of academic science in Ukraine. For a comparative analysis of the research themes of monographs and abstracts of dissertation papers defended by the scientists of the institute, a statistical method of research was used.
Development of theoretical electrical engineering at the Institute of electrodynamics of NAS Ukraine (1991–2017)
Keywords: теоретична електротехніка; Інститут електродинаміки НАН України; нелінійні кола; електромагнітне поле; моделювання електромагнітних процесів; theoretical electrical engineering; Institute of Electrodynamics of the National Academy of Sciences of Ukraine; nonlinear circles; electromagnetic field; modeling of electromagnetic processes